Functional proteomic analysis of Ankaferd® Blood Stopper - Duygu Özel Demiralp; İbrahim C. Haznedaroğlu; Nejat Akar (Turkish Journal of Hematology, 2010)
Objective: Ankaferd® Blood Stopper (ABS) comprises a standardized mixture of the plants Thymus vulgaris, Glycyrrhiza glabra, Vitis vinifera, Alpinia officinarum, and Urtica dioica. The basic mechanism of action for ABS is the formation of an encapsulated protein network that provides focal points for vital erythrocyte aggregation. ABS–induced protein network formation with blood cells, particularly erythrocytes, covers the primary and secondary hemostatic system without disturbing individual coagulation factors. Materials and Methods: To understand the effect mechanisms of ABS on hemostasis, a proteomic analysis using 2D gel electrophoresis and mass spectrometer was performed. Results: Proteins of plant origin in Ankaferd® were NADP-dependent-malic enzyme, ribulose bisphosphate-carboxylase-large chain, maturase K, ATP synthase subunit-beta, ATP synthase subunit-alpha, chalcone-flavanone isomerase-1, chalcone-flavanone isomerase-2, and actin-depolymerizing factor. Furthermore, functional proteomic studies revealed that proteins resembling human peptides have been detected within Ankaferd®, including ATP synthase, mucin-16 (CD164 sialomucin-like 2 protein), coiled-coil domain containing 141 hypothetical protein LOC283638 isoform 1, hypothetical protein LOC283638 isoform 2, dynactin 5, complex I intermediate-associated protein 30, mitochondrial, NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, TP synthase, H+ transporting, mitochondrial actin binding 1 isoform, LIM domain and actin binding 1 isoform a, LIM domain and actin binding 1 isoform b, spectrin alpha non erythrocytic 1, prolactin releasing hormone receptor, utrophin, tet oncogene family member 2 isoform b, protein phosphatase 1 regulatory subunit 12A, NIMA (never in mitosis gene a)-related kinase, ATP-binding cassette protein C12, Homo sapiens malic enzyme 1, mitochondrial NADP(+)-dependent malic enzyme 3, ME2 protein, nuclear factor 1 B-type, abhydrolase domain-containing protein 12B, E3 SUMO-protein ligase PIAS2, alpha-1, 2-glucosyltransferase ALG10-A, cofilin, non-muscle isoform, 18 kDa phosphoprotein, p18, actin-depolymerizing factor (ADF), twinfilin-1, ankyrin repeat and FYVE domain-containing protein 1, usherin precursor, urotensin II receptor, interleukin 4, and midkine. Conclusion: Proteomic analysis of Ankaferd® represents a true basis for the upcoming Ankaferd® studies focusing on its wound healing, hemostatic, anti-infective, antineoplastic, and preservative biological actions.